Partial Purification of Cholinesterase from Pangasius pangasius using Affinity Chromatography - Tham, Lik Gin; Shukor, Mohd Yunus; Syed, Mohd Arif; Shamaan, Nor Aripin; Othman, Ahmad Razi (Journal of Environmental Microbiology and Toxicology, 2017)
An affinity chromatography column to purify AChE was developed using procainamide as the ligand coupled with the epoxy activated Sephacryl-S1000 as the modified matrix. From this study, the procainamide matrix was found to be capable of binding acetylcholinesterase (AChE) from the brain of Pangasius pangasius efficiently, with percentage of yield of approximately 51.97% and a purification fold of 7.52. The value for Michaelis-Menten (Km app) was 0.1265 mM and maximal velocity (Vmax app) of the partially purified enzyme was 0.6981 Âµmol/min/mg, with a substrate specificity in the sequence ofâ€” acetylthiocholine iodide (ATC) > propinylcholine iodide (PTC) > butyrylcholine iodide (BTC). This strongly suggest that using this column, AChE can be purified successfully and efficiently. SDS-PAGE indicated a reduced band intensity, indicating that the procainamide-based affinity chromatography column produces acceptable partially purified enzyme adequate for the application in the rapid detection of carbamate and organophosphate (OP) at the large scale.